Meta-PREVI Grammar. (December 2014) - Mendes, Leticia Teixeira; Celani, Gabriela; Beirão, José Nuno
This paper describes part of a wider research that aimed at using Shape Grammar to generate more diverse and interesting urban spaces in Brazilian Social Housing developments. A shape grammar corresponding to design patterns was inferred from the PREVI Lima urban plan developed by C. Alexander [1] in the 1970s. The grammar was inferred from the plan layout and from the text instructions (or pattern descriptions) presented by Alexander, and can be applied to design new plans within a wider formal universe than what the plan layout would suggest. The final section of the paper points towards the development of generic grammars as a way of encapsulating good qualities of certain design projects and applying them to new situations.